Prediction of in situ strengths and matrix cracking in composites under transverse tension and in-plane shear - Pedro P. Camanho (2006)
A criterion for matrix failure of laminated composite plies in transverse tension and in-plane shear is developed by examining the mechanics of transverse matrix crack growth. Matrix cracks are assumed to initiate from manufacturing defects and can propagate within planes parallel to the fiber direction and normal to the ply mid-plane. Fracture mechanics models of cracks in unidirectional laminates, embedded plies and outer plies are used to determine the onset and direction of propagation of crack growth. The models for each ply configuration relate ply thickness and ply toughness to the corresponding in situ ply strength. Calculated results for several materials are shown to correlate well with experimental results.